Effect of Hole Transporting Material on Perovskite Based Solar Cells Using One Dimensional Solar Cell Capacitance Simulator (SCAPS-1D) - SULEMAN Kamaldeen Olasunkanmi (Global Scientific Journal, 2019)
In this research, the simulation of Sandwiched Perovskite Based Solar Cells (PSCs) was investigated using a computer based software known as solar cell capacitance simulator (SCAPS-1D). The effect of Hole Transporting Material (HTM) on the sandwiched perovskite was determined by the electrical. The solar cell structures used are n-FTO/ZnO/p-CZTS/p-PSC/p CZTS/HTM and n-FTO/ZnO/p-CZTS/p-PSC/p-CZTS. The simulations were performed under ambient temperature (300K) and AM 1.5 Sun of the Solar spectrum parameters (Voc, Jsc, FF) and efficiency generated by the SCAPS-1D. From the results obtained, the model band gap for the two devices and graphs were plotted and the efficiencies recorded. It was observed that with the increase of perovskite thickness from 50 to 500 nm, the efficiencies of the sandwiched perovskite increases. It was also observed that the device with HTM had a greater efficiency than the device without the HTM. The efficiencies of 20.56 % and 15.53 % were recorded for the sandwiched perovskite with HTM and the sandwiched Perovskite without HTM. The continuous increase in the efficiencies of the device with HTM shows that it has a positive effect on the perovskite.
Keywords: Perovskite; sandwiched; Hole Transporting Material (HTM); efficiency.